KORELASI PERILAKU SISWA TERHADAP SASTRA DAN KETERAMPILAN MEMAHAMI CERITA - Puspasari, Fitri; Umbarasari, Thea; Nurhuda, Zamzam; Audina, Salsa (Ensiklopedia of Journal, 2025)
This study aims to determine the relationship between students' attitudes toward literature and their ability to understand story content. The background of this study is based on the fact that many students experience difficulties in understanding literary texts due to their low level of appreciation for literary works. The method used was a quantitative correlational study involving 40 Grade XII students from SMKN 8 Kota Serang as respondents. The instruments used included a questionnaire to measure attitudes toward literature and an essay test to measure the ability to understand stories. The analysis results showed a positive and significant relationship between students' attitudes toward literature and their ability to understand stories, with a correlation coefficient of 0.629 and a high significance value. These findings indicate that an increase in positive attitudes toward literature has an impact on improving students' literacy skills in understanding story texts. This study recommends the need to strengthen appreciative attitudes through creative and student-centered literature learning strategies.Keywords: Student attitudes; literature; story comprehension; literature learning.